(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Erdheim–Chester disease (ECD) is a rare non-Langerhans cell histiocytosis characterized by multisystem infiltration of foamy histiocytes and progressive fibrosis. Owing to its heterogeneous clinical presentation and rarity, diagnosis is often delayed and requires histopathological and immunohistochemical confirmation. Aim & Objectives: To report a rare case of Erdheim–Chester disease presenting with refractory anemia, highlighting the role of bone marrow biopsy and immunohistochemistry in diagnosis, and emphasizing the importance of early molecular evaluation for targeted therapy and improved patient outcomes. Case Presentation: A 47-year-old female presented with generalized weakness, easy fatigability, intermittent diarrhea, insomnia, and refractory anemia. Routine laboratory and radiological investigations were inconclusive. Peripheral smear revealed normocytic normochromic anemia. Bone marrow aspiration was inadequate due to fibrosis, following which a trephine biopsy was performed. Histopathological examination showed diffuse infiltration by spindle-shaped and foamy histiocytes associated with stromal fibrosis. Immunohistochemistry demonstrated positivity for CD68 and CD163, while CD1a and Langerin (CD207) were negative, excluding Langerhans cell histiocytosis. CD3 highlighted admixed reactive T-lymphocytes. Based on histomorphological and immunophenotypic findings, a diagnosis of Erdheim–Chester disease was established. The patient received supportive treatment and was advised molecular testing for BRAF mutation analysis and further systemic evaluation for targeted therapy planning. Results: Bone marrow biopsy with immunohistochemistry confirmed Erdheim–Chester disease, showing CD68 and CD163 positivity with negative CD1a and CD207. The patient received supportive treatment and was advised BRAF mutation analysis for targeted therapy. Conclusion: This case highlights the importance of considering Erdheim–Chester disease in patients presenting with unexplained constitutional symptoms and infiltrative marrow pathology. Bone marrow biopsy with immunohistochemistry plays a pivotal role in diagnosis. Early recognition and molecular evaluation are essential for timely initiation of targeted therapy and improved clinical outcomes.